IJIMAI Editor's Note - Vol. 3 Issue 4 - Magreñán, Á. Alberto (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This special issue, Teaching Mathematics using new and classic tools, concentrates on the practical and experimental teaching in advanced Mathematics in Engineering. The selected papers deal with the most relevant issues in the field, such as Mathematical learning and other different subjects in which Mathematics are needed, Advanced Mathematics, the development of different studied using Masive Open Online courser (MOOCs) or even the history of E-Learning and Mathematics. The result is a collection of experimental validations, mathematical papers and MOOCs studies which constitutes a clear contribution to the state of the art.
Keywords: education; editors note; mathematics; IJIMAI